Perioperative Nursing Care dengan Tindakan Pyelithotomy pada Nefrolithiasis - Slamed Ardiyansyah Mahmud; Suhermi S; Rizqy Iftitah Alam; Arifuddin Arifuddin (Wal'afiat Hospital Journal, 2025)
Nephrolithiasis, commonly known as kidney stones, is a condition in which stones or crystals form in the kidneys, leading to impaired urination and causing pain. One of the surgical l treatments for staghorn kidney stones is open pyelolithotomy, a procedure to remove large kidney stones. This study aims to analyze Nursing Care for patients undergoing Perioperative pyelolithotomy. The research employs a qualitative case study approach, focusing on the preoperative and postoperative Nursing Care for patients diagnosed with nephrolithiasis and undergoing pyelolithotomy. The findings of the study show that based on Nursing assessment, two main diagnoses were identified: anxiety, related to insufficient information about the procedure, as evidenced by the patient appearing anxious and tense. The intervention provided was anxiety reduction, which effectively alleviated the patient's anxiety. The second diagnosis was acute pain, related to the physical trauma of surgery, as evidenced by the patient grimacing, being restless, and experiencing an increased heart rate. The intervention used was pain management, which included medication and Quranic murottal therapy. In conclusion, the study indicates that interventions such as deep breathing relaxation techniques and education about kidney stones to reduce anxiety, along with the use of murottal therapy and medication for pain relief, significantly improved the effectiveness of Nursing Care during the Perioperative period for nephrolithiasis patients.